Analisis Ergonomi Postur Kerja Pekerja Pandai Besi Berdasarkan SNI 9011:2021 di Dusun Talwa Kabupaten Sumbawa - Rohmandani Putri, Desi; Hudaningsih, Nurul; Mashabai, Ismi; Ulfaturrahmi (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
The work of traditional blacksmiths in Talwa, Sumbawa Regency, is still done manually with awkward work postures, excessive use of energy, heat exposure, and vibration, thus risking musculoskeletal disorders (MSDs). This condition shows that there is a gap in research related to the application of ergonomics in the traditional small industry sector. This study aims to analyze the level of ergonomic risk in blacksmith workers using the Skeletal Muscle Disorder (GOTRAK) assessment and the SNI 9011:2021 ergonomic potential hazard checklist, and develop recommendations for improvement. The method used was descriptive quantitative on five workers, with data collection through the GOTRAK questionnaire and SNI 9011:2021 checklist. The results show high risk (score >8) in the shoulders, upper and lower back, arms, and hands, and moderate risk (score 6-7) in the neck, elbows, hips, thighs, knees, calves, and feet. Ergonomic potential hazard scores ranged from 9 to 21, with the main exposures from bending postures, wrist bending, power grip >5 kg, vibration without dampening, high temperature, and static standing. Implementation of SNI 9011:2021 in traditional small industries and ergonomic recommendations to improve safety, comfort, and productivity.